Automatic Extraction of Diaphragm Motion and Respiratory Pattern from Time-sequential Thoracic MRI - Windra Swastika; Yoshitada Masuda; Takashi Ohnishi; Hideaki Haneishi (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Thoracic time-sequential MRI can be used to assess diaphragm motion pattern without exposing radiation to subject. Clinicians may employ the motion to evaluate the severeness of chronic obstructive pulmonary disease (COPD). This study proposed a novel method of diaphragm motion extraction method on time-sequential thoracic MRI in sagittal plane. Otsu’s threshold and active contour algorithm are used to obtain diaphragm boundary. An automatic diaphragm motion tracking and extraction of respiratory pattern are also performed based on the diaphragm boundary. A total of 1200 frames time-sequential MRI in sagittal plane was obtained for total of 15 subjects (8 healthy volunteers and 7 COPD patients). The proposed method successfully extracts diaphragm motion and respiratory patterns for both healthy volunteers and COPD patients. DOI: http://dx.doi.org/10.11591/telkomnika.v14i2.7375